A lei de concentração do crime: estudo de caso para Belo Horizonte, Minas Gerais - Antônio Hot Pereira de Faria (Confins)
This paper aims to explore the mapping of crimes within micro places from the Law of Crime Concentration perspective, using the city of Belo Horizonte as the spatial focus and employing data from 2018 to 2021 as the temporal demarcation. The methodological path included mapping violent crimes and thefts in Belo Horizonte, joining crime events points into lines for crime analysis concentration by street segments. The results indicated that for the case of Belo Horizonte, there is a perfect alignment between the collected data and that described by the Law of Crime Concentration. In 2021, there was a concentration of 25% of thefts in 0.40% of Belo Horizonte's street segments; 50% of the same type of offense occurred in 2.56% of the street segments. Violent crimes also showed a similar pattern. In 2021, 25% of violent crimes occurred in 0.96% of street segments; 50% of these offenses occurred in 3.42% of the street segments. Besides, there was a significant inequality of crime concentration, as the Gini coefficients indicated an average value close to 0.90, signifying that crime in the city is very concentrated in small portions of its territory. Another theoretical prediction that was confirmed was the stability of hot spots. In Belo Horizonte, the data indicated that there was a stability of maintenance of status in terms of crime concentration for the street segments over the analysis period (2018 to 2021) above 70% for both crimes analysed. The results suggest that despite the general decrease in crime rates during the period, hot spots remained hot. This finding not only provides better support for the implementation of crime prevention strategies through Hot Spot Policing but also strengthens the field of crime geography and environmental criminology with empirical analysis work.